2018
DOI: 10.1159/000492024
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Ankyrin Mutations in Hereditary Spherocytosis: A Case Report and Review of the Literature

Abstract: Background/Aims: Hereditary spherocytosis (HS) is a common pediatric hemolytic anemia caused by congenital red blood cell defects. HS due to ankyrin 1 (ANK1) mutations is the most common type. We explored an ANK1 mutation from an HS patient and reviewed the literature. Methods: We detected the mutation in a Chinese family in which 2 members were diagnosed with HS by next-generation sequencing. The proband was diagnosed with HS in the newborn period, based on clinical manifestations, laboratory data, and family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Ankyrin mutations are the most common cause of HS in Northern European populations and were first reported in German patients [1]. In recent years, several new pathogenic mutations have been identified relative to ANK1-mutated HS in some Asian countries, such as China, Japan and Korea [17]. Thus far, over 80 different mutations have been confirmed in ANK1-mutated HS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankyrin mutations are the most common cause of HS in Northern European populations and were first reported in German patients [1]. In recent years, several new pathogenic mutations have been identified relative to ANK1-mutated HS in some Asian countries, such as China, Japan and Korea [17]. Thus far, over 80 different mutations have been confirmed in ANK1-mutated HS patients.…”
Section: Discussionmentioning
confidence: 99%
“…HS can be diagnosed at any age and with any severity, and the description of case reports varies greatly. Luo et al identified a novel splice-site ANK1 mutation (c.2960 + 2T > G) in newborns based on significantly decompensated anaemia and unexplained jaundice in early infancy, family history, and haematological data [17]. In general, patients with HS may have a severe phenotype early in life, and the symptoms may disappear with age.…”
Section: Discussionmentioning
confidence: 99%
“…[5] HS is a product of heterogenous alteration in one of the six genes, most often in the ankyrin gene (ANK1) which encodes for ankyrin. [6,7] Other commonly mutated genes are SPTB, SLC4A1, EPB42 and SPTA1 encoding for spectrin β-chain, anion exhanger 1(band 3), protein 4.2 and the spectrin α-chain respectively. [7,8] The characteristics of HS vary from asymptomatic to fulminant hemolytic anemia.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier issue of Acta Haematologica , Luo et al [6] reported a novel ankyrin mutation using NGS and have reviewed the relevant literature focusing on the pediatric/neonatal population. The propositus is a female neonate who presented with total bilirubin of 65 µmol/L and direct bilirubin of 19.4 µmol/L.…”
mentioning
confidence: 99%
“…Luo et al’s study [6] not only reports a novel splice site mutation in ANK1 gene, it also emphasizes the utility of NGS in the diagnosis of these complex multigene disorders. Identifying the underlying genetic cause not only helps with the management of the patient, it also facilitates accurate genetic counselling and helps in guidance regarding the predicted severity of clinical phenotype.…”
mentioning
confidence: 99%